SIKAP SEBAGAI VARIABEL INTERVENING ANTARA DUKUNGAN KELUARGA DENGAN PERILAKU KONTROL RUTIN PASIEN HIPERTENSI DI PALEMBANG - Koerniawan, Dheni; Indaryati, Sri; Istiyani, Sry (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Target of hypertension management is normal blood pressure or at least in stable condition. Stabilize blood pressure can be obtained if patient done regular checkup to monitor and evaluate his/her health condition. Regular checkup behavior influenced by patient attitude to making decision of his/her blood pressure control and family support to that decision. This study aimed to identify intervening variable between attitude and family support to regular checkup behavior of hypertensive patient in Talang Betutu Public Health Center. This study used analytic survey to 44 hypertensive patients with purposive sampling by questionnaire. Path analysis with logistic regression approach used to conduct conceptual model of influence between variables. Logistic regression result showed there was significant influence between attitude to regular checkup behavior (b: 2.616; p: 0.001) but not between family support to regular checkup behavior (b: 0.238; p: 0.756). Path analysis given model that attitude being intervening variable between family supports and regular checkup behavior so family support had indirect correlation and influence to regular checkup behavior. Thus, nurse education strategies pointed to increasing awareness of hypertensive patient about his/her health condition and effort to maintain blood pressure in control or stable as precaution and decreasing risk of complication.   Keywords:hypertension, attitude, family support, regular checkup behavior, logistic regression, path analysis